Global, Not Yet Local: Media Coverage of Climate Change and Environment Related Challenges in Latvia - Kleinberga, Vineta (Information & Media, 2022)
Media are essential actors in transmitting, contesting and embedding the attitudes towards climate change, yet media performance in post-communist countries has been relatively little researched. Informed by conceptual frameworks of strategic narratives, agenda-setting and framing, this paper investigates the media coverage of climate change and environment related issues in Latvia. The paper demonstrates the representation of climate change and environment related issues in Latvian and Russian-speaking traditional and online media, using quantitative data analysis of 3753 media articles, video and audio broadcasts from August 2020 till January 2021, as well as qualitative content analysis of seven peaks.The findings reveal a significant amount of climate change and environment related articles and broadcasts in Latvian media. News agencies and public broadcasters are the most important media segments in terms of publishing, whereas online media are prior in terms of the audiences reached. International efforts emerge as a dominant theme in the media coverage, while climate change per se receives a minor journalist attention. Both observations confirm a low level of climate change domestication in the Latvian media. Media reliance on political and government information sources and prepackaged material suggests a high potential for official political narratives to spread, yet the persuasive power of strategic narratives remains blurred as the perception side is highly underreported.
Keywords: climate change; strategic narratives; media projection; domestication; information sources; Latvia